Doped positive electrode precursor material and preparation method and application thereof
By using ultrasonic assisted technology to dopulate the doping process of the positive electrode precursor material, the problems of poor uniformity, high energy consumption and many processes in the existing processes are solved, and efficient and uniform doping effect is achieved, and the performance of lithium-ion batteries is improved.
Patent Information
- Application Number
- CN202411906235.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing doping process of positive electrode precursor material has problems such as poor uniformity, high energy consumption and many processes, resulting in low production efficiency, reduced pass rate and increased production costs.
Ultrasonic assisted technology is used to dopant elements, and the doping reaction is carried out by flowing the main metal salt mixed solution, precipitant solution and complexing agent solution in conjunction with the main metal salt mixture, and then mixing it with the doping salt solution for ultrasonic assisted doping to ensure uniform dispersion of the doped elements.
The production efficiency and pass rate of doped positive electrode precursor materials are improved, the process flow is simplified, and the energy consumption is reduced. The obtained material has high spherical shape, narrow particle size distribution, high tap density and excellent electrochemical performance, which improves the first-effect, magnification and cycling performance of lithium-ion batteries.
Smart Images

Figure CN119706973A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and relates to a doped positive electrode precursor material and a preparation method and use thereof Background Art
[0002] Lithium-ion batteries are green and environmentally friendly batteries, including liquid lithium-ion batteries or solid lithium-ion batteries. Compared with traditional nickel-cadmium batteries and nickel-metal hydride batteries, lithium-ion batteries have significant advantages such as high operating voltage, high power density, good cycle performance, long charge and discharge life, and low self-discharge rate, and effectively solve the environmental pollution problem of cadmium in nickel-cadmium batteries. The above characteristics of lithium-ion batteries can realize repeated conversion between electrical energy and chemical energy, and are considered to be a very efficient energy storage device. They have been widely used in electric vehicles, electric bicycles, energy storage devices and portable electronic devices.
[0003] Whether it is a liquid lithium-ion battery or a solid lithium-ion battery, the performance of the positive electrode material directly affects the various performance indicators of the lithium-ion battery, so the positive electrode material of the lithium-ion battery is a key factor in the development of lithium-ion batteries. As we all know, the number of battery cycles is limited by the positive electrode material. In the battery production cost, the cost of the positive electrode material accounts for more than 30% of the total material cost. Therefore, the preparation of low-cost and high-cycle positive electrode materials is the main research goal.
[0004] In order to improve the cycle stability of positive electrode materials, the current research and development focus is mostly on the modification of positive electrode materials, such as doping and coating. However, during the sintering process of positive electrode materials, doping usually has uneven doping. At the same time, in order to ensure the doping amount and improve the doping uniformity, the sintering temperature is increased or the sintering process is increased. For example, CN111682198 discloses a step-by-step doped ternary positive electrode material and a preparation method thereof. The preparation method comprises the following steps: fully mixing the ternary material precursor, the first lithium source and the dopant a, sintering at 750-950°C for 2-8h to obtain a lithiated product; fully mixing the lithiated product, the second lithium source and the dopant b, sintering at 750-950°C for 2-8h to obtain a step-by-step doped ternary positive electrode material. However, the doping method provided above has the disadvantages of poor uniformity, high energy consumption and many processes.
[0005] Therefore, in recent years, researchers have gradually applied element doping to precursors to improve the uniformity of element doping, reduce the sintering process, and improve the electrochemical performance of positive electrode materials. By exploring the optimal doping elements and concentrations, they strive to maximize performance, minimize costs and environmental impacts, and ensure the development of high energy density, durable and safe battery technology. At present, the preparation of doped positive electrode materials (especially positive electrode precursors of nickel-cobalt-manganese, nickel-manganese, nickel-cobalt-aluminum systems) mainly adopts the coprecipitation method. In the coprecipitation process, the growth process of the ternary precursor is usually controlled by adjusting the process parameters such as salt solution concentration, complexing agent concentration, pH value, and solid content; with the limitations of precursor particle size, specific surface area, TD and other indicators, the doping of elements in the process needs to be more precisely controlled, which will lead to problems such as low product production efficiency, reduced pass rate, and increased production costs.
[0006] CN113659129A discloses a multi-element doping scheme, which sets different reaction stages according to different particle sizes. In the first stage, all metal salt solutions, complexing agents and precipitant solutions are added to a reactor. In the second stage, the above solutions are passed into a reactor with ammonia water as the base liquid for reaction. Although the scheme provided by the above document can dope three elements at the same time, the percentage of the doping elements in the entire experimental process still needs to be manually controlled, which can easily cause problems such as inaccurate doping content, low production efficiency, and increased manufacturing costs.
[0007] Therefore, how to solve the problems of low product production efficiency, reduced qualified rate, increased production cost, etc. in the above-mentioned cathode precursor doping process is currently in urgent need of research. Summary of the invention
[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a doped positive electrode precursor material and a preparation method and use thereof. The preparation method provided by the present invention has a simple doping process for elements in the positive electrode precursor material, and the content of the doped elements is controllable, thereby improving the production efficiency and qualified rate of the doped positive electrode precursor material, and facilitating large-scale production; and the prepared doped positive electrode precursor material has high sphericity, narrow particle size distribution, high tap density, and excellent electrochemical performance.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a doped positive electrode precursor material, the preparation method comprising the following steps:
[0011] Adding the main metal salt mixed solution, the precipitant solution and the complexing agent solution in parallel to perform a co-precipitation reaction to obtain a positive electrode precursor material to be doped;
[0012] The positive electrode precursor material to be doped is mixed with a doping salt solution, and a doping treatment is performed with the assistance of ultrasound to obtain a doped positive electrode precursor material.
[0013] The preparation method provided by the present invention performs doping of doping elements in a positive electrode precursor material with the assistance of ultrasound. Ultrasound can achieve uniform dispersion of particles at the microscopic level, and can ensure that the doping elements are uniformly doped in the positive electrode precursor to be doped. The process is simple, the content of the doping elements is controllable, the production efficiency and the qualified rate of the doped positive electrode precursor material are improved, and large-scale production is easy. The prepared doped positive electrode precursor material has high sphericity, narrow particle size distribution, high tap density, and excellent electrochemical performance, thereby improving the first efficiency, rate and cycle performance of the lithium-ion battery.
[0014] In the present invention, the positive electrode precursor material to be doped is first prepared, and then ultrasonic-assisted doping of the doping element is performed, so that the doping element can be evenly distributed in the secondary particles and the doping content can be controlled; directly performing ultrasonic assistance in the co-precipitation process will increase energy consumption and cause unnecessary waste.
[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0016] Preferably, the main metal elements in the main metal salt mixed solution include at least nickel and / or manganese.
[0017] Preferably, the main metal element in the main metal salt mixed solution further includes cobalt and / or aluminum.
[0018] The doped positive electrode precursor material provided by the present invention, wherein the main metal elements are conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments according to actual needs; for example, it can be nickel-cobalt-manganese, nickel-manganese, nickel-cobalt, nickel-cobalt-aluminum, manganese-rich system, nickel-cobalt-manganese-aluminum, etc.; and the specific molar ratio of the above main metal elements is calculated by adding the molar ratios of all elements to 1, and can be adaptively selected and adjusted according to actual needs.
[0019] For example, when the main metal elements in the main metal mixed salt solution contain nickel, cobalt and manganese at the same time, the molar ratio of nickel, cobalt and manganese is (0-1):(0-1):(0-1) and does not include 0 and 1, and the sum of the molar ratios of the three is 1.
[0020] Preferably, the flow ratio of the main metal salt mixed solution, the precipitant solution and the complexing agent solution is (5.5-6):(2-2.5):(1-2), for example, 5.5:2:1, 5.5:2.3:1, 5.5:2.5:1, 5.5:2.5:2, 5.5:2:1, 5.5:2:1.5, 5.5:2:2, 5.8:2:1, 6:2:1, 6:2:2 or 6:2.5:1, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In the present invention, by regulating the flow rate ratio of the main metal salt mixed solution, the precipitant solution and the complexing agent solution to be (5.5-6):(2-2.5):(1-2), a doped positive electrode precursor material with high sphericity, narrow particle size distribution and high tap density can be better obtained.
[0022] Preferably, during the coprecipitation reaction, the pH value is maintained at 10-12, for example, 10, 10.3, 10.5, 10.8, 11, 11.3, 11.5, 11.8 or 12, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the stirring speed of the coprecipitation reaction is 250-400rpm, for example, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm, 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm, 360rpm, 370rpm, 380rpm, 390rpm or 400rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, the reaction temperature of the coprecipitation reaction is 50-60°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the reaction time of the coprecipitation reaction is 70 to 100 h, for example 70 h, 75 h, 80 h, 85 h, 90 h, 95 h or 100 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, the solution after the coprecipitation reaction is sequentially subjected to solid-liquid separation and drying treatment to obtain the positive electrode precursor material to be doped.
[0027] Preferably, the median particle size D50 of the positive electrode precursor material to be doped is 3 to 5 μm, for example, 3 μm, 3.3 μm, 3.5 μm, 3.8 μm, 4 μm, 4.3 μm, 4.5 μm, 4.8 μm or 5 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] In the present invention, the median particle size D50 of the positive electrode precursor material to be doped obtained by regulating the coprecipitation reaction is 3 to 5 μm, which is more conducive to the uniformity of the doping elements, the doping efficiency and the stability of the positive electrode material.
[0029] Preferably, the solid content of the doped positive electrode precursor material in the mixed solution is 40-45%, for example 40%, 41%, 42%, 43%, 44% or 45%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] In the present invention, the solid content of the doped positive electrode precursor material in the mixed solution is further adjusted to 40-45%, which can make the particles have higher density, better sphericity, more concentrated particle size distribution, and blurred grain boundaries of primary particles.
[0031] Preferably, the concentration of the doping salt solution is 1000-4000 mg / L, for example, 1000 mg / , 1500 mg / , 2000 mg / , 2500 mg / , 3000 mg / , 3500 mg / or 4000 mg / , but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] The present invention can achieve effective regulation of the specific doping amount of the doping element, and the appropriate solid content and doping solution concentration help to ensure uniform doping of the elements, more complete reaction, smooth subsequent sintering process and ultimately obtain a material with excellent performance.
[0033] Preferably, the ultrasonic-assisted temperature is 20-30°C, for example 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In the present invention, the doping of doping elements can be carried out at room temperature without the need for excessively high temperatures, thus simplifying the preparation process.
[0035] Preferably, the frequency of the ultrasonic assistance is 20 to 40 kHz, for example 20 kHz, 23 kHz, 25 kHz, 28 kHz, 30 kHz, 33 kHz, 35 kHz, 38 kHz or 40 kHz, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the power of the ultrasonic assistance is 100-800 W, for example 100 W, 150 W, 200 W, 250 W, 300 W, 350 W, 400 W, 450 W, 500 W, 550 W, 600 W, 650 W, 700 W, 750 W or 800 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the ultrasonic-assisted rotation speed is 400-600 rpm, for example 400 rpm, 425 rpm, 450 rpm, 475 rpm, 500 rpm, 525 rpm, 550 rpm, 575 rpm or 600 rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In the present invention, the frequency of the ultrasonic assistance is further adjusted to 20-40kHz and / or the power of the ultrasonic assistance is 100-800W and / or the rotation speed of the ultrasonic assistance is 400-600rpm, which can better improve the doping effect, increase the reaction rate and uniformity, improve the solubility of the metal salt, and optimize the morphology and particle size distribution of the particles.
[0039] Preferably, the ultrasound-assisted time is 60 to 120 min, for example 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] It should be noted that, in the present invention, after the ultrasonic-assisted doping process is completed, conventional washing and drying treatments are performed to obtain the final doped positive electrode precursor material.
[0041] As a preferred technical solution, the preparation method comprises the following steps:
[0042] The main metal salt mixed solution, the precipitant solution and the complexing agent solution are added in parallel at a flow ratio of (5.5-6):(2-2.5):(1-2), and a co-precipitation reaction is carried out at 50-60° C. and a rotation speed of 250-400 rpm under the condition of a pH value of 10-12, followed by solid-liquid separation and drying to obtain a positive electrode precursor material to be doped;
[0043] The positive electrode precursor material to be doped and the doping salt solution are mixed, wherein the solid content of the positive electrode precursor material to be doped in the mixed solution is 40-45%, and the doping treatment is performed for 60-120 minutes by ultrasonic assistance, and the conditions of ultrasonic assistance are: temperature of 20-30° C., frequency of 20-40 kHz, power of 100-800 W, and rotation speed of 400-600 rpm to obtain a doped positive electrode precursor material;
[0044] Wherein, the main metal elements in the main metal salt mixed solution include at least nickel and / or manganese.
[0045] It should also be noted that the specific type and concentration of the salt solution, the type and concentration of the precipitant, the solution and concentration of the complexing agent, and the selection of the doping element in the doping salt in the present invention are all conventional technical solutions, which can be used for the preparation of the corresponding positive electrode precursor materials. The present invention is applicable to all of them.
[0046] Optionally, the salt solution in the main metal salt mixed solution includes but is not limited to at least one of sulfate, chloride, acetate or nitrate.
[0047] Optionally, the concentration of the salt solution in the main metal salt mixed solution is 1 to 10 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L or 10 mol / L, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Optionally, the precipitant includes but is not limited to at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or sodium bicarbonate.
[0049] Optionally, the concentration of the precipitant solution is 1 to 15 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L or 15 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the complexing agent includes at least one of ammonia water, ethylenediaminetetraacetic acid (EDTA), sodium oxalate, sodium citrate, salicylic acid, citric acid, nitrilotriacetic acid, glacial acetic acid or hydroxyformic acid.
[0051] Optionally, the concentration of the complexing agent solution is 1 to 15 mol / L, for example, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L, 12 mol / L, 13 mol / L, 14 mol / L or 15 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Optionally, when the complexing agent is ammonia water, the mass concentration of the complexing agent solution is 10% to 40%, for example 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] Optionally, the doping elements in the doping salt solution include but are not limited to at least one of Mg, Ca, Sr, Ba, Y, La, V, Nb, Ta, Cr, Mo, Zn, B, Ga, Ge, Sn, Sb, Bi, Zr, Ti, W, Ta, Al, Ce, Si, Hf or Y.
[0054] Optionally, the salt solution in the doped salt solution includes but is not limited to at least one of sulfate, chloride, acetate or nitrate.
[0055] In a second aspect, the present invention provides a doped positive electrode precursor material, wherein the doped precursor material is prepared by the preparation method described in the first aspect.
[0056] In a third aspect, the present invention provides a doped positive electrode material, wherein the doped positive electrode material is obtained by mixing and sintering the doped positive electrode precursor material as described in the second aspect with a lithium source.
[0057] The present invention does not specifically limit the specific preparation method of the doped positive electrode material prepared from the doped positive electrode precursor material provided by the present invention, and the present invention is applicable to any preparation process that can be known within a reasonable range by those skilled in the art.
[0058] Exemplarily, the present invention provides a method for preparing a doped positive electrode material, which specifically comprises:
[0059] The lithium source and the doped positive electrode precursor material are mixed, sintered, crushed and sieved to obtain the doped positive electrode material.
[0060] Preferably, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium nitrate or lithium chloride.
[0061] Preferably, the molar ratio of the sum of the molar amounts of all metal elements in the doped positive electrode precursor material to the lithium in the lithium source is 1:(1-1.3), for example 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.2, 1:1.25 or 1:3, etc., but is not limited to the listed values, and other unlisted values within this numerical range are also applicable.
[0062] Preferably, the sintering is performed in an oxygen-containing atmosphere, including a pure oxygen atmosphere or an air atmosphere.
[0063] Preferably, the sintering temperature is 700-1200°C, for example 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] Preferably, the sintering time is 4 to 20 h, for example 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] In a fourth aspect, the present invention further provides a lithium-ion battery, wherein the lithium-ion battery comprises the doped positive electrode material as described in the third aspect.
[0066] Preferably, the lithium ion battery comprises a liquid lithium ion battery and / or a solid lithium ion battery, preferably a solid lithium ion battery.
[0067] Compared with the prior art, the present invention has the following beneficial effects:
[0068] The preparation method provided by the present invention performs doping of doping elements in a positive electrode precursor material with the assistance of ultrasound. Ultrasound can achieve uniform dispersion of particles at the microscopic level, and can ensure that the doping elements are uniformly doped in the positive electrode precursor to be doped. The process is simple, the content of the doping elements is controllable, the production efficiency and the qualified rate of the doped positive electrode precursor material are improved, and large-scale production is easy. The prepared doped positive electrode precursor material has high sphericity, narrow particle size distribution, high tap density, and excellent electrochemical performance, thereby improving the first efficiency, rate and cycle performance of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0069] Figure 1 A process flow chart of a specific preparation process of a doped positive electrode precursor material and a doped positive electrode material provided in an embodiment of the present invention.
[0070] Figure 2 This is a SEM image of the doped positive electrode precursor material provided in Example 1.
[0071] Figure 3 This is a SEM image of the doped positive electrode precursor material provided in Example 9.
[0072] Figure 4 This is the SEM image of the doped positive electrode precursor material provided in Example 13.
[0073] Figure 5 This is the SEM image of the doped positive electrode precursor material provided in Comparative Example 1. DETAILED DESCRIPTION
[0074] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0075] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0076] Example 1
[0077] This embodiment provides a method for preparing a doped positive electrode precursor material, and the preparation method is as follows:
[0078] (1) Under the protection of nitrogen atmosphere, nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a mixed sulfate solution with a total metal ion concentration of 1 mol / L in a molar ratio of Ni:Co:Mn=6:1:3. 3 In the reactor, 1000L of pure water was added, the mass concentration ratio of sodium hydroxide to ammonia water was 2:1, the mass concentration of ammonia water was 15%, and the ternary metal solution, sodium hydroxide and ammonia water were flowed into the reactor at a flow ratio of 5.5:2:2 according to the set flow rate. During the reaction, the pH of the solution was about 10.3-10.5, the stirring rate was 350rpm, the temperature was maintained at 60°C, the reaction was continued for 95h, and the D50 reached the standard value of 5μm and stopped;
[0079] (2) centrifugally drying and collecting the above-mentioned completely reacted solution to obtain the positive electrode precursor material to be doped;
[0080] (3) The positive electrode precursor material to be doped is mixed with a tungsten sulfate solution with a concentration of 3000 mg / L, wherein the solid content of the positive electrode precursor material to be doped in the mixed solution is 40%, and an ultrasonic-assisted doping reaction is performed, wherein the reaction temperature is 25°C, the ultrasonic frequency is 40 kHz, the ultrasonic power is 600 W, the stirring speed is 500 rpm, the ultrasound is continued for 120 min, and the doped positive electrode precursor material is washed and dried to obtain a doped positive electrode precursor material uniformly doped with tungsten element.
[0081] Example 2
[0082] (1) Under the protection of nitrogen atmosphere, nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a mixed sulfate solution with a total metal ion concentration of 1 mol / L in a molar ratio of Ni:Co:Mn=6:1:3. 3 In the reactor, 1000L of pure water was added, the mass concentration ratio of sodium hydroxide to ammonia water was 2:1, the mass concentration of ammonia water was 15%, and the ternary metal solution, sodium hydroxide and ammonia water were flowed into the reactor at a flow ratio of 5.5:2:2 according to the set flow rate. During the reaction, the pH of the solution was about 10.3-10.5, the stirring rate was 350rpm, the temperature was maintained at 60°C, the reaction was continued for 95h, and the D50 reached the standard value of 5μm and stopped;
[0083] (2) centrifugally drying and collecting the above-mentioned completely reacted solution to obtain the positive electrode precursor material to be doped;
[0084] (3) The positive electrode precursor material to be doped is mixed with a tungsten sulfate solution with a concentration of 1000 mg / L, wherein the solid content of the positive electrode precursor material to be doped in the mixed solution is 45%, and an ultrasonic-assisted doping reaction is performed, wherein the reaction temperature is 25°C, the ultrasonic frequency is 20 kHz, the ultrasonic power is 100 W, the stirring speed is 400 rpm, and the ultrasonic treatment is continued for 60 minutes, followed by washing and drying to obtain a doped positive electrode precursor material uniformly doped with tungsten element.
[0085] Example 3
[0086] This embodiment provides a method for preparing a doped positive electrode precursor material, and the preparation method is as follows:
[0087] (1) Under the protection of nitrogen atmosphere, nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a mixed sulfate solution with a total metal ion concentration of 1 mol / L in a molar ratio of Ni:Co:Mn=6:1:3. 3In the reactor, 1000L of pure water was added, the mass concentration ratio of sodium hydroxide to ammonia water was 2:1, the mass concentration of ammonia water was 15%, and the ternary metal solution, sodium hydroxide and ammonia water were flowed into the reactor at a flow ratio of 5.5:2:2 according to the set flow rate. During the reaction, the pH of the solution was about 10.3-10.5, the stirring rate was 350rpm, the temperature was maintained at 60°C, the reaction was continued for 70h, and the D50 reached the standard value of 3μm and stopped;
[0088] (2) centrifugally drying and collecting the above-mentioned completely reacted solution to obtain the positive electrode precursor material to be doped;
[0089] (3) The positive electrode precursor material to be doped is mixed with a tungsten sulfate solution with a concentration of 4000 mg / L, wherein the solid content of the positive electrode precursor material to be doped in the mixed solution is 43%, and an ultrasonic-assisted doping reaction is performed, wherein the reaction temperature is 25°C, the ultrasonic frequency is 30 kHz, the ultrasonic power is 800 W, the stirring speed is 500 rpm, and the ultrasonic treatment is continued for 90 minutes, followed by washing and drying to obtain a doped positive electrode precursor material uniformly doped with tungsten element.
[0090] Example 4
[0091] This embodiment provides a method for preparing a doped positive electrode precursor material, and the preparation method is as follows:
[0092] (1) Under the protection of nitrogen atmosphere, nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a mixed sulfate solution with a total metal ion concentration of 2 mol / L in a molar ratio of Ni:Co:Mn=8:1:1. 3 In the reactor, 1000L of pure water was added, the mass concentration ratio of sodium hydroxide to ammonia water was 2:1, the mass concentration of ammonia water was 20%, and the ternary metal solution, sodium hydroxide and ammonia water were flowed into the reactor at a flow ratio of 6:2.5:1 according to the set flow rate. During the reaction, the pH of the solution was about 11.8-12, the stirring rate was 250rpm, the temperature was maintained at 50°C, the reaction was continued for 85h, and the D50 reached the standard value of 4μm and stopped;
[0093] (2) centrifugally drying and collecting the above-mentioned completely reacted solution to obtain the positive electrode precursor material to be doped;
[0094] (3) The positive electrode precursor material to be doped is mixed with a zirconium sulfate solution with a concentration of 2000 mg / L, wherein the solid content of the positive electrode precursor material to be doped in the mixed solution is 40%, and an ultrasonic-assisted doping reaction is performed, wherein the reaction temperature is 25°C, the ultrasonic frequency is 40 kHz, the ultrasonic power is 600 W, the stirring speed is 500 rpm, the ultrasound is continued for 120 min, and the mixture is washed and dried to obtain a doped positive electrode precursor material uniformly doped with tungsten element.
[0095] Example 5
[0096] The difference between this embodiment and embodiment 1 is that the solid content of the positive electrode precursor material to be doped in the mixed solution in step (3) of this embodiment is 35%.
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Example 6
[0099] The difference between this embodiment and embodiment 1 is that the solid content of the positive electrode precursor material to be doped in the mixed solution in step (3) of this embodiment is 50%.
[0100] The rest of the preparation methods and parameters were the same as those in Example 1.
[0101] Example 7
[0102] The difference between this embodiment and embodiment 1 is that the ultrasonic frequency in step (3) of this embodiment is 10 kHz.
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Example 8
[0105] The difference between this embodiment and embodiment 1 is that the ultrasonic frequency in step (3) of this embodiment is 50 kHz.
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 9
[0108] The difference between this embodiment and embodiment 1 is that the ultrasonic power in step (3) of this embodiment is 50W.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 10
[0111] The difference between this embodiment and embodiment 1 is that the ultrasonic power in step (3) of this embodiment is 850W.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Embodiment 11
[0114] The difference between this embodiment and embodiment 1 is that in the ultrasonic-assisted process in step (3) of this embodiment, the stirring speed is 300 rpm.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Example 12
[0117] The difference between this embodiment and embodiment 1 is that in the ultrasonic-assisted process in step (3) of this embodiment, the stirring speed is 700 rpm.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Embodiment 13
[0120] The difference between this embodiment and embodiment 1 is that in step (3) of this embodiment, the ultrasonic time is 30 minutes.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Comparative Example 1
[0123] The difference between this embodiment and embodiment 1 is that in step (3) of this embodiment, ultrasonic-assisted treatment is not performed, and the positive electrode precursor material to be doped is directly mixed with the tungsten sulfate salt solution, and the solid content of the positive electrode precursor material to be doped in the mixed solution is 40%. The reaction is carried out, wherein the reaction temperature is 25°C, the stirring speed is 500 rpm, and the stirring is continued for 60 minutes to obtain a ternary precursor material uniformly doped with tungsten element.
[0124] The rest of the preparation methods and parameters were the same as those in Example 1.
[0125] Comparative Example 2
[0126] The difference between this comparative example and Example 1 is that in this comparative example, ultrasound-assisted means is added during the coprecipitation reaction stage, and the specific preparation process is as follows:
[0127] (1) In an ultrasonic environment with an ultrasonic frequency of 40 kHz and an ultrasonic power of 600 W, under the protection of a nitrogen atmosphere, nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a mixed sulfate solution with a total metal ion concentration of 1 mol / L at a molar ratio of Ni:Co:Mn=6:1:3, and tungsten sulfate was prepared into a tungsten sulfate solution with a concentration of 3000 mg / L. 3 In the reactor, 1000L of pure water was added, the mass concentration ratio of sodium hydroxide to ammonia water was 2:1, the mass concentration of ammonia water was 15%, and the ternary metal solution, sodium hydroxide, ammonia water and tungsten sulfate salt solution were flowed into the reactor at a flow ratio of 5.5:2:2:1 according to the set flow rate. During the reaction, the pH of the solution was about 10.3-10.5, the stirring rate was 350rpm, the temperature was maintained at 60°C, the reaction was continued for 95h, and the D50 reached the standard value of 5μm and stopped;
[0128] (2) The above-mentioned solution after the complete reaction is washed, centrifuged, dried, and collected to obtain the doped positive electrode precursor material.
[0129] Figure 1 The process flow chart of the specific preparation process of the doped positive electrode precursor material and the doped positive electrode material provided in the embodiment of the present invention is shown. Figure 1 The process flow diagram in the embodiment 1-13 includes the complete process flow from preparing the doped precursor material to preparing the positive electrode material.
[0130] Figure 2 The SEM image of the doped positive electrode precursor material provided in Example 1 is shown. Figure 2 It can be clearly seen that the primary particles of the doped positive electrode precursor material of Example 1 are distinct, the secondary particles have good sphericity and good dispersibility.
[0131] Figure 3 The SEM image of the doped positive electrode precursor material provided in Example 9 is shown. Figure 2 , the sphericity of the particles decreased, indicating that the ultrasonic power has an effect on the sphericity. The stronger the power, the higher the sphericity.
[0132] Figure 4 The SEM image of the doped positive electrode precursor material provided in Example 13 is shown. Figure 2 , the primary particles are not uniform, indicating that the ultrasonic time has a great influence on the formation of the primary morphology of the particles. The longer the ultrasonic time, the more conducive it is to the uniform distribution of the primary particles.
[0133] Figure 5 The SEM image of the doped positive electrode precursor material provided for Comparative Example 1 is shown. From the morphology, it can be seen that without adding ultrasonic dispersion, the sphericity of the morphology is poor and the particles are uneven.
[0134] from Figures 2 to 5 It can be seen that the doped positive electrode precursor material provided in the embodiment of the present invention is screened for suitable preparation conditions by changing the solid content, ultrasonic power, ultrasonic frequency, ultrasonic time, and stirring speed during the reaction process. The prepared ternary precursor has good stability and uniformity during the sintering process of the positive electrode material.
[0135] [Battery assembly and performance testing]
[0136] (1) Preparation of positive electrode materials:
[0137] The doped positive electrode precursor materials provided in Examples 1-13 and Comparative Examples 1-2 were fully mixed with lithium hydroxide at a molar ratio of 1:1.05, calcined at 930° C. for 14 h in an air atmosphere, naturally cooled, crushed, and sieved to obtain a doped positive electrode material.
[0138] (2) Battery assembly:
[0139] The doped positive electrode material and conductive carbon black were mixed in a mass ratio of 70:30 as the positive electrode; 100 mg of lithium zirconium phosphate (LiZr2(PO4)3(LZP)) was weighed as a solid electrolyte, and lithium foil (Li) was selected as the negative electrode. The pressed solid-state mold battery was assembled in the order of positive electrode, lithium zirconium phosphate, and lithium sheet. The assembly pressure was 300 MPa. Finally, a stainless steel shell was used to fix the mold and maintain the pressure. After the assembly was completed, it was allowed to stand at room temperature for 10 hours to obtain a stable solid-state lithium-ion battery.
[0140] (3) Performance test:
[0141] a) First performance and cycle: The assembled battery was subjected to EIS test on an Autolab electrochemical workstation, charged to 4.3 V (potential relative to Li) at a rate of 0.1C (1C = 200 mAh / g), allowed to stand, and then discharged to 2.5 V, also allowed to stand; subsequent cycles were repeated as needed, and the cycle performance was tested at room temperature at 1.9 V-4.3 V and a rate of 0.1C for charge and discharge.
[0142] b) Rate performance: The assembled batteries were tested at different rates of 0.1C, 0.2C, 0.5C and 1C at 2.9-4.3V and 25°C. The ratio of the discharge capacity of 1C / 0.1C is the rate performance.
[0143] The test results of the above tests are shown in Table 1.
[0144] Table 1
[0145]
[0146]
[0147] In summary, the preparation method provided by the present invention performs doping of doping elements in the positive electrode precursor material with the assistance of ultrasound. Ultrasound can achieve uniform dispersion of particles at the microscopic level, and can ensure that the doping elements are uniformly doped in the positive electrode precursor to be doped. The process is simple, and the content of doping elements is controllable, thereby improving the production efficiency and qualified rate of the doped positive electrode precursor material, and facilitating large-scale production. The prepared doped positive electrode precursor material has high sphericity, narrow particle size distribution, high tap density, and excellent electrochemical properties, thereby improving the first efficiency, rate and cycle performance of lithium-ion batteries.
[0148] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a doped positive electrode precursor material, characterized in that: The preparation method comprises the following steps: Adding the main metal salt mixed solution, the precipitant solution and the complexing agent solution in parallel to perform a co-precipitation reaction to obtain a positive electrode precursor material to be doped; The positive electrode precursor material to be doped is mixed with a doping salt solution, and a doping treatment is performed with the assistance of ultrasound to obtain a doped positive electrode precursor material.
2. The preparation method according to claim 1, characterized in that: The main metal element in the main metal salt mixed solution includes at least nickel and / or manganese; Preferably, the main metal element in the main metal salt mixed solution further includes cobalt and / or aluminum; Preferably, the flow ratio of the main metal salt mixed solution, the precipitant solution and the complexing agent solution is (5.5-6):(2-2.5):(1-2); Preferably, during the coprecipitation reaction, the pH value is maintained at 10 to 12; Preferably, the stirring speed of the coprecipitation reaction is 250-400 rpm, the reaction temperature of the coprecipitation reaction is 50-60° C., and the reaction time of the coprecipitation reaction is 70-100 h.
3. The preparation method according to claim 1 or 2, characterized in that: Sequentially subjecting the solution after the coprecipitation reaction to solid-liquid separation and drying treatment to obtain the positive electrode precursor material to be doped; Preferably, the median particle size D50 of the positive electrode precursor material to be doped is 3 to 5 μm.
4. The preparation method according to any one of claims 1 to 3, characterized in that The solid content of the positive electrode precursor material to be doped in the mixed solution is 40-45%; Preferably, the concentration of the doped salt solution is 1000-4000 mg / L.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The temperature of the ultrasound assistance is 20-30°C; Preferably, the frequency of the ultrasound assistance is 20 to 40 kHz; Preferably, the power of the ultrasonic assistance is 100-800W; Preferably, the ultrasonic-assisted rotation speed is 400-600 rpm; Preferably, the ultrasound-assisted treatment time is 60 to 120 minutes.
6. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: The main metal salt mixed solution, the precipitant solution and the complexing agent solution are added in parallel at a flow ratio of (5.5-6):(2-2.5):(1-2), and a co-precipitation reaction is carried out at 50-60° C. and a rotation speed of 250-400 rpm under the condition of a pH value of 10-12, followed by solid-liquid separation and drying to obtain a positive electrode precursor material to be doped; The positive electrode precursor material to be doped and the doping salt solution are mixed, wherein the solid content of the positive electrode precursor material to be doped in the mixed solution is 40-45%, and the doping treatment is performed for 60-120 minutes by ultrasonic assistance, and the conditions of ultrasonic assistance are: temperature of 20-30° C., frequency of 20-40 kHz, power of 100-800 W, and rotation speed of 400-600 rpm to obtain a doped positive electrode precursor material; Wherein, the main metal elements in the main metal salt mixed solution include at least nickel and / or manganese.
7. A doped positive electrode precursor material, characterized in that: The doped precursor material is prepared by the preparation method according to any one of claims 1 to 6.
8. A doped positive electrode material, characterized in that: The doped positive electrode material is obtained by mixing and sintering the doped positive electrode precursor material as claimed in claim 7 with a lithium source.
9. A lithium ion battery, characterized in that: The lithium-ion battery comprises the doped positive electrode material as claimed in claim 8.
10. The lithium ion battery according to claim 9, characterized in that: The lithium ion battery includes a liquid lithium ion battery and / or a solid lithium ion battery, preferably a solid lithium ion battery.
Citation Information
Patent Citations
Multi-element-doped ternary precursor and preparation method thereof
CN113659129A
Positive electrode material of lithium ion battery and preparation method thereof
CN103050684A
Preparation method of lithium ion battery positive-electrode material precursor
CN103943846A
Ternary positive electrode material doped with Er and Zr metal ions and preparation method thereof
CN107732234A
Double ultrasonic coupling device and method for preparing lithium-rich manganese-based positive anode material and precursor thereof
CN109395647A